2012
DOI: 10.1128/aem.07199-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Mapping of pAR060302, a bla CMY-2 -Positive Broad-Host-Range IncA/C Plasmid

Abstract: The multidrug resistance-encoding plasmids belonging to the IncA/C incompatibility group have recently emerged among Escherichia coli and Salmonella enterica strains in the United States. These plasmids have a unique genetic structure compared to other enterobacterial plasmid types, a broad host range, and a propensity to acquire large numbers of antimicrobial resistance genes via their accessory regions. Using E. coli strain DH5␣ harboring the prototype IncA/C plasmid pAR060302, we sought to define the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
2
26
1
Order By: Relevance
“…Integrons are very prevalent in plasmids and are generally related to antibiotic resistance (111). Transcriptional analysis has shown that integron cassettes are among the highest-expressed plasmid genes, representing an important potential source of fitness cost to host bacteria (112)(113)(114).…”
Section: Mechanisms For Minimizing Plasmid Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrons are very prevalent in plasmids and are generally related to antibiotic resistance (111). Transcriptional analysis has shown that integron cassettes are among the highest-expressed plasmid genes, representing an important potential source of fitness cost to host bacteria (112)(113)(114).…”
Section: Mechanisms For Minimizing Plasmid Costsmentioning
confidence: 99%
“…To date, only a handful of studies have investigated the genetic basis of plasmid fitness costs (23,(25)(26)(27)(28) or the transcriptional effects of plasmids on the bacterial host (23,25,113,131). In our experience, the best way to investigate the molecular mechanisms underlying the fitness costs of plasmids is to first obtain a compensated clone from the parental plasmid-carrying strain (22,23).…”
Section: Integrative Analysis Of Plasmid Costsmentioning
confidence: 99%
“…This ParA protein has similarity to ParA of IncP plasmids, while IncA/C ParB contains both ParB and KorB domains (1). These genes are transcribed at low levels, similar to repA (21). Another putative partitioning gene, stbA, is found in a separate genetic location.…”
mentioning
confidence: 99%
“…IncA/C plasmids also possess a putative toxin-antitoxin (TA) system. The TA genes are strongly transcribed, suggesting the system is functionally active in the postsegregation killing of plasmid-free progeny (21). Moreover, attempts to construct deletion mutants of the antitoxin component proved to be lethal to the cell (22).…”
mentioning
confidence: 99%
“…Plasmids are a modular mosaic of mobile genetic elements (MGEs) which the plasmids can carry and transfer between individual bacteria of different species by lateral gene transfer (also called horizontal gene transfer) (1)(2)(3). In so doing, the plasmids can transfer these genes to the bacterial chromosome or can gain more drug resistance genes.…”
mentioning
confidence: 99%